Evoking the Principle of Subsidiarity: Merit for a SADC Protocol for Children - MUSAVENGANA WINSTON THEODORE CHIBWANA (African Journal of Governance and Development, 2020)
Children’s rights civil society in the Southern African Development Community (SADC) is pushingfor a protocol for children to be developed. The effort that these organisations are exerting raisesobvious questions: Is there a need for such a protocol and what will be the value of it? Are notthe country ratifications at international and regional levels enough? Are we not burdening themember states by asking them to have another instrument when they seem to be strugglingwith the existing ones? How will accountability be ensured? The paper provides a rationalefor the children’s protocol and prospective content that will be encapsulated therein. One ofthe main reasons is that the emerging children’s rights issues are not adequately covered inexisting children’s rights normative frameworks such as the African Charter on the Rights andWelfare of the Child (ACRWC) and the United Nations Convention on the Rights of theChild (UNCRC). Consequently, there is no jurisprudence of how member states can deal withthese emerging issues. Further, SADC has 27 protocols dealing with a plethora of issues. Theavailable protocols do not systematically address children’s rights in line with the four cardinalprinciples. It is a realisation of these issues that has prompted children’s rights civil society tolobby SADC to come up with a SADC protocol for children.